Pelayanan Jasa Impor Barang Dalam Masa Pandemi - Supartini Supartini; Iswanto Iswanto; Ningrum Astriawati; Vivid Dekanawati; Nanda Kevin Hamzah Alfanzuri (Dinamika Bahari, 2022)
Import is a very important activity for a country, from these activities the state obtains income or meets the needs of society. The impact of the pandemic affects companies engaged in the import of goods, by enforcing WFH (Work From Home) employees, or doing work in the office with strict health protocols, the company requires employees to do a rapid antigen test every 1 or 2 weeks. The purpose of this study is to describe the services of importing goods during the pandemic. This research is a qualitative research with a descriptive method.The data collection method is divided into 3 parts, namely: direct observation method in the field, interview method, document method. From the results of the study, it was concluded that the service of importing goods during the pandemic implements an online system service. Slow networks are obstacles that cause all service processes to customers to be slow, so they require a good network for the smooth process of activities. Due to the pandemic there is a special demand for importers, which requires all truck drivers/crew entering the warehouse to be tested, this results in additional time and costs incurred.